Multicentre variability of MRI-based medial temporal lobe volumetry in Alzheimer's disease - Teipel, Stefan; Ewers, Michael; Wolf, Stefanie; Jessen, Frank; Kölsch, Heike; Arlt, Sönke; Luckhaus, Christian; Schönknecht, Peter; Schmidtke, Klaus; Heuser, Isabella; Frölich, Lutz; Ende, Gabriele; et al. (Psychiatry research. Neuroimaging, 2010)
Magnetic resonance imaging (MRI)-based volumetry of medial temporal lobe regions is among the best established biomarker candidates of Alzheimer's disease (AD) to date. This study assessed the effect of multicentre variability of MRI-based hippocampus and amygdala volumetry on the discrimination between patients with Alzheimer's disease (AD) and mild cognitive impairment (MCI) and on the association of morphological changes with ApoE4 genotype and cognition. We studied 113 patients with clinically probable AD and 150 patients with amnestic MCI using high-resolution MRI scans obtained at 12 clinical sites. We determined effect sizes of group discrimination and random effects linear models, considering multicentre variability. Hippocampus and amygdala volumes were significantly reduced in AD compared with MCI patients using data pooled across centres. Multicentre variability did not significantly affect the power to detect a volume difference between AD and MCI patients. Among cognitive measures, delayed recall of verbal and non-verbal material was significantly correlated with hippocampus and amygdala volumes. Amygdala and hippocampus volumes were not associated with ApoE4 genotype in AD or MCI. Our data indicate that multicentre acquisition of MRI data using manual volumetry is reliable and feasible for cross-sectional diagnostic studies, and they replicate essential findings from smaller scale monocentre studies.
Gesehen am 26.10.2023